Sustainable Design and Manufacturing 2019 : Proceedings of the 6th International Conference on Sustainable Design and Manufacturing (KES-SDM 19) /: Proceedings of the 6th International Conference on Sustainable Design and Manufacturing (KES-SDM 19). (2019) - Unknown
No abstract available